2009
DOI: 10.1007/s10722-009-9413-7
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic diversity within native Iranian almond (Prunus spp.) species and their breeding potential

Abstract: A total of 137 accessions from 18 wild almond species were collected from Iran and leaf and fruit traits were characterized. Also evaluated were flowering and ripening date, self-incompatibility and kernel bitterness. An extensive phenotypic diversity was found both among and within species. Differences in average leaf dimensions among and within species were associated with average rainfall but not altitude of collection site. Adjacent accessions located in drier areas had smaller leaf dimensions than those l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
64
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 22 publications
12
64
0
Order By: Relevance
“…In the present study, kernel weight ranged between 0.46 and 2.28 g. Zeinalabedini et al [11] recorded kernel weight from Determining relationships between various traits can help breeders set goals for parental partner selection and breeding [10]. Strong correlations were observed between many of the studied traits (table III).…”
Section: Resultsmentioning
confidence: 47%
See 1 more Smart Citation
“…In the present study, kernel weight ranged between 0.46 and 2.28 g. Zeinalabedini et al [11] recorded kernel weight from Determining relationships between various traits can help breeders set goals for parental partner selection and breeding [10]. Strong correlations were observed between many of the studied traits (table III).…”
Section: Resultsmentioning
confidence: 47%
“…As a place of origin of the almond, the genetic diversity of almond germplasm in Iran has been widely investigated by the use of hierarchical and principal component analyses [10][11][12]. Iranian almond germplasm is regarded as one of the most diverse and valuable of almond genetic resources in the world.…”
Section: Introductionmentioning
confidence: 99%
“…Morphological characters were used in phenotypic observations to characterize the genetic diversity of almond species, but their interactions with the environment and the small number of characters [20][21][22] prompted the use of other more discriminating techniques. Currently, DNA markers are widely used in studies of genetic diversity and the clarification of certain research questions, among others, those concerning their genetic origin [9].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, fruit breeding programmes have increased interest in wild germplasm as a source of useful traits (e.g. resistance to diseases, stress) to be introduced into the genome of cultivated plants (Fischer and Fischer, 2004;Hajjar and Hodgkin, 2007;Sorkheh et al, 2009;De la Rosa et al, 2014). Indeed, Klepo et al (2013Klepo et al ( , 2014 and Arias-Calderon et al (2015) demonstrated the usefulness of wild olive for generating new genotypes with relevant characteristics.…”
Section: Introductionmentioning
confidence: 99%